Immunological profile of a Plasmodium vivax AMA-1 N-terminus peptide-carbon nanotube conjugate in an infected Plasmodium berghei mouse model (2008)
We have covalently conjugated an N-terminus Plasmodium vivax apical membrane antigen-1 (AMA-1) peptide to functionalized carbon nanotubes (f-CNT). Immunological characterization of this molecular conjugate revealed that the immunogen-AMA-1 peptide was appropriately presented after being conjugated to CNTs as well as being recognized by BALB/c polyclonal antibodies. Subsequent experiments lead us to assess the AMA-1 peptide alone, as well as the CNT-peptide conjugate regarding rodent malarial infection. Remarkably, the peptide effectively controlled and delayed Plasmodium berghei-challenged animals' parasitaemia. The peptide-CNT conjugate displayed similar immunological properties to the peptide alone by protecting or delaying malarial infection. The peptide presentation by f-CNT to the immune system thus constitutes a promising approach for synthetic malarial vaccine formulation since the immunogen peptide conformation is well preserved. © 2008 Elsevier Ltd. All rights reserved.